Addressing Implementation Challenges of Minimum Service Standards in Local Government Using Soft System Methodology: A Case Study of Bekasi City, Indonesia - Desimaria, Maharina; Rahayu, Amy Yayuk Sri; Junarti, Junarti; Novia, Reni (Nyimak: Journal of Communication, 2024)
Minimum Service Standards (MSS) are specific provisions that must be fulfilled by local governments as a concurrent obligation targeted to reach 100% every year. However, as of 2023, Bekasi City has not achieved the set targets. The MSS Service Quality Achievement Index in Bekasi City is still relatively low, with all 6 MSS falling under the "Unfinished" category. This indicates problems in MSS implementation, including issues related to policy, planning, budgeting, and execution involving policymakers, implementers, and service recipients. This study aims to map the challenges in implementing MSS in Bekasi using Soft System Methodology (SSM) analysis and provide recommendations for addressing the identified issues. This research adopts a qualitative approach with action research methodology. Data collection techniques include analyzing relevant documents to understand the problem situation and conducting SSM's seven stages of analysis. This study contributes to the literature by applying SSM to understand and enhance policy implementation at the local level, which can be adapted to similar contexts in neighboring Malaysia and Singapore. The findings serve as a reference for improving MSS implementation and enhancing public service quality.Keywords: Minimum Service Standards, Soft System Methodology, policy implementation, Bekasi City AbstrakStandar Pelayanan Minimal (SPM) merupakan ketentuan khusus yang harus dipenuhi oleh pemerintah daerah sebagai kewajiban bersama yang ditargetkan mencapai 100% setiap tahun. Namun, hingga tahun 2023, Kota Bekasi belum mencapai target yang ditetapkan. Indeks Pencapaian Kualitas Layanan SPM di Kota Bekasi masih tergolong rendah, di mana dari 6 SPM, semuanya berada dalam kategori belum tercapai. Hal ini menunjukkan adanya permasalahan dalam implementasi SPM, baik dari aspek kebijakan, perencanaan, penganggaran, hingga pelaksanaan yang melibatkan aktor-aktor kebijakan, pelaksana, dan penerima layanan. Penelitian ini bertujuan untuk memetakan permasalahan dalam penerapan SPM di Kota Bekasi menggunakan analisis Soft System Methodology (SSM) serta memberikan rekomendasi untuk tindak lanjut dari permasalahan yang telah dipetakan. Penelitian ini menggunakan pendekatan kualitatif dengan metode action research. Teknik pengumpulan data dilakukan dengan memahami dokumen-dokumen terkait untuk memberikan gambaran situasi masalah dan melakukan analisis dengan menerapkan tujuh tahapan SSM. Hasil penelitian ini berkontribusi pada literatur dengan menerapkan SSM untuk memahami dan meningkatkan implementasi kebijakan di tingkat lokal, yang dapat diadaptasi di sistem serupa seperti Malaysia dan Singapura. Temuan ini dapat digunakan sebagai acuan untuk memperbaiki implementasi SPM dan meningkatkan kualitas layanan publik.Kata Kunci: Standar Pelayanan Minimal, Soft System Methodology, implementasi kebijakan, Kota Bekasi